2017
DOI: 10.1128/aac.01288-16
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Food Effect on Pharmacokinetic Parameters of ABX464 Administered Orally to Healthy Male Subjects

Abstract: ABX464 is an antiviral that provides a novel approach to the reduction and control of HIV infection. Investigation of food influence is important in the optimization of treatment. An open-label, food effect, randomized study which included 2 groups of 24 subjects each was carried out to assess the bioavailability and safety of single (group 1) and repeated (group 2) oral doses of ABX464 (50 mg) under fed or fasted conditions. The maximum concentration (C max ) and the area under the concentration-time curve fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 15 publications
2
4
1
Order By: Relevance
“…This study demonstrated that there were no substantial differences in the PK characteristics of the two compounds between HIV-infected and non-HIV-infected subjects. It was also confirmed that the food effect of both compounds was comparable to that reported in noninfected subjects ( 14 ).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This study demonstrated that there were no substantial differences in the PK characteristics of the two compounds between HIV-infected and non-HIV-infected subjects. It was also confirmed that the food effect of both compounds was comparable to that reported in noninfected subjects ( 14 ).…”
Section: Discussionsupporting
confidence: 83%
“…In these studies, whereas HAART was very efficient in reducing the viral load to undetectable levels after 2 to 3 weeks in all treated mice, only 30% of mice treated with ABX464 had an undetectable viral load after the same treatment period, and longer treatment with ABX464 was required to achieve a viral load reduction in more mice. In addition, the PK data reported here and in previous studies demonstrated that the parent compound has a very short half-life of approximately 1 h compared to the metabolite ABX464-NGlc, which has a t 1/2 of approximately 100 h ( 13 , 14 ). The maximum concentration in plasma ( C max ) of the metabolite was also approximately 160-fold higher than that of the parent compound.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations